Cost-effectiveness analysis of first-line tislelizumab plus chemotherapy for recurrent or metastatic nasopharyngeal cancer - Pei, Zhengda; Xiao, Ningping; Yang, Pei (Frontiers in Pharmacology, 2023)
Introduction: The RATIONALE-309 trial confirmed the significant efficacy and safety of tislelizumab plus chemotherapy in patients with recurrent or metastatic nasopharyngeal carcinoma (R/M NPC). However, the economic benefits of this regimen are unclear. Therefore, this study aimed to evaluate the cost-effectiveness of adding tislelizumab to chemotherapy for R/M NPC from the perspective of the Chinese healthcare system. Methods: A Markov model was established to simulate the costs and outcomes of tislelizumab plus chemotherapy versus chemotherapy. The survival data came from the RATIONALE-309 trial. Only direct medical costs were considered, and utility values were referred to the literature. The incremental cost-effectiveness ratio (ICER) was used as the main outcome measure. Sensitivity analysis was performed to assess the effect of parameter uncertainty on the model. Additionally, subgroup analyses were performed. Results: The basic analysis showed that the cost of tislelizumab plus chemotherapy ($33,693) was $17,711 higher than that of chemotherapy ($15,982), but it also gained 1.05 QALYs more (2.72 QALYs vs 1.67 QALYs), with an ICER of $16,859/QALY, which was lower than the willing-to-pay (WTP) of $36,289/QALY. The factors that most influenced the model were the utility of PD, the cost of tislelizumab, and the risk of platelet count decreased in tislelizumab plus chemotherapy group. The subgroup analysis also demonstrated that tislelizumab plus chemotherapy was cost-effective in the whole population regardless of EBV DNA level and PD-L1 expression level. Conclusion: Compared with chemotherapy alone, tislelizumab plus chemotherapy was cost-effective for the treatment of R/M NPC in China.